Green Nanotechnology Approach for Mitigating Trichoderma Threats using Ajwain-derived Silver Nanoparticles - Rajwant Kaur; Harjeet Singh; Gurinder Singh; Harpreet Kaur (International Journal of Scientific Research in Science and Technology, 2026)
Trichoderma species , particularly those responsible for the green Mold disease , pose a major threat to the commercial cultivation of button mushroom (Agaricus bisporus) , leading to a significant yield losses ,reduced quality, and increased production costs, conventional chemical fungicide have shown declining effectiveness due to resistance development and environmental concerns , creating an urgent need for eco- friendly alternatives . in the present study a bio fungicide was formulated using Trachyspermum ammi (ajwain) seed extract , known for its antimicrobial activity and antifungal phytochemicals, enhanced through green synthesis of silver nanoparticles(ag NPs) using the same extract as the reducing and stabilizing agent this green synthesis combined the intrinsic antifungal activity if ajwain with the high surface reactivity of a nano silver, producing a synergetic effect against Trichoderma species ,and interfere with some spore germination thereby inhibiting the colonization in mushroom substrates. The use of plant- based reducing agents ensures non- toxic , sustainable nanoparticles production, making the formulation suitable for agricultural applications. Overall, the ajwain -mediated Ag Np’s bio fungicide demonstrates string potential as an effective and environmentally safe to mange mushroom cultivation.
Keywords: Mushroom cultivation; Trichoderma species; silver nanoparticles; Green Mold